CCAFS Climate-Smart Village Approach: Is CSA practice testing linked to climate services delivery? - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
A fundamental principle of CCAFS from its inception is that we work from the bottom up, co-developing and evaluating appropriate technologies and practices with farmers in participatory approaches. In 2011, we established benchmark sites for joint fieldwork in three regions (East and West Africa and South Asia), and initiated a program of action research that would allow multi-location, long-term and community -based trialing of holistic portfolios of adaptation options. Designed to learn about the social, cultural, economic and institutional processes of adaptation and mitigation, and to support the design of implementation strategies, the Benchmark sites quickly led to the emergence of the concept of Climate-Smart Villages (CSVs). Borne out of India’s states of Punjab and Bihar (CCAFS Annual Report 2011), this new concept started in 2012, and stresses aspects related to: the multi-stakeholder partnership involved, the focus on maximizing synergies across a portfolio of tailored technical and institutional climate-smart agricultural interventions and the need to associate local innovation with scaling-up processes. CSVs are envisioned as “models” of local actions that enhance productivity, increase incomes, achieve climate resilience and enable climate mitigation (CCAFS Brochure 2013).